Eucalyptus camaldulensis Seeds as a Potential Source of Beneficial Compounds: High-Performance Liquid Chromatography – Photodiode Array – Mass Spectrometry (HPLC-PDA-MS/MS) Profiling of Secondary Metabolites and the Assessment of the Biological Effects. (3rd July 2023) - Tir, Meriam; Mufti, Afoua; Feriani, Anouar; Saadaoui, Ezzeddine; El Cafsi, M'Hammed; Tlili, Nizar
Abstract: The Eucalyptus species is traditionally used to cure many diseases. The goal of the present work was to study the phytochemical components of the Eucalyptus camaldulensis seed extract (EC) and to explore the antioxidant and the enzyme inhibitory effects. High-performance liquid chromatography – photodiode array – mass spectrometry analysis (HPLC-PDA-MS/MS) revealed the presence of fifty-seven molecules in the Eucalyptus camaldulensis extract. The main compounds detected were malic acid, gallic acid, and ellagic acid. The results showed that the extract had significant dose–response antioxidant properties and also inhibitory capacity against α-amylase and α-glucosidase. These results highlight the importance of Eucalyptus seeds as a source of biomolecules with beneficial effects.